2020
DOI: 10.1038/s41598-020-70430-2
|View full text |Cite
|
Sign up to set email alerts
|

A single-center retrospective safety analysis of cyclin-dependent kinase 4/6 inhibitors concurrent with radiation therapy in metastatic breast cancer patients

Abstract: Cyclin dependent kinases 4/6 (CDK4/6) inhibitors gained an essential role in the treatment of metastatic breast cancer. Nevertheless, data regarding their use in combination with radiotherapy are still scarce. We performed a retrospective preliminary analysis of breast cancer patients treated at our Center with palliative radiation therapy and concurrent CDK4/6 inhibitors. Toxicities were measured according to CTCAE 4.0, local response according to RECIST 1.1 or PERCIST 1.0 and pain control using verbal numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 37 publications
(50 reference statements)
0
19
0
Order By: Relevance
“…Although the results of these trials are limited by the small number of the sample, the clinical and radiological outcomes are promising. Future studies with a larger population and a longer follow-up will validate these results [64,77].…”
Section: Combination Of Radiotherapy and Systemic Treatmentmentioning
confidence: 64%
“…Although the results of these trials are limited by the small number of the sample, the clinical and radiological outcomes are promising. Future studies with a larger population and a longer follow-up will validate these results [64,77].…”
Section: Combination Of Radiotherapy and Systemic Treatmentmentioning
confidence: 64%
“…22,23 Furthermore, hypofractionated radiotherapy is often applied showing several cases of G3 skin and gastrointestinal toxicity. [13][14][15][16][17][18] However, the nature and limited size of these studies, including our study, make it difficult to reliably predict the absolute risk of increased toxicity.…”
Section: Discussionmentioning
confidence: 94%
“…13,14 Two retrospective studies show that the combination is generally safe, but the authors also report a G3 ileitis in one patient (10 Â 3 Gy) and G3 skin toxicity in two patients (radiation dose not mentioned). 15,16 Grade 3 esophagitis is described in two case reports (30 Â 2 Gy and 5 Â 4 Gy), combined with G3 dermatitis in one patient. 17,18 Also, a conference abstract reports unexpected pronounced pulmonary fibrosis and radiation pneumonitis.…”
mentioning
confidence: 94%
“…Taken together, our results suggest that CDK4/6 inhibition + RT is a promising strategy to decrease recurrence and increase local disease control across ER+ and TNBC and that RB may be a potential biomarker for efficacy. Concerns about the safety of concurrent CDK4/6 inhibition and RT remain, and to date, small studies exploring outcomes in patients with MBC receiving palliative radiation and CDK4/6 inhibitor therapy have conflicting results regarding toxicity, depending on the dose/fractionation of radiation and the regions targeted in the metastatic setting (visceral organs) (61)(62)(63)(64). Reassuringly, no studies to date have demonstrated more pronounced side effects of CDK4/6 inhibitors, such as cytopenias and skin desquamation, in women receiving concurrent therapy to the breast or axillary regions.…”
Section: Discussionmentioning
confidence: 99%
“…Concerns about the safety of concurrent CDK4/6i and RT remain, and to date, small studies exploring outcomes in patients with metastatic breast cancer receiving palliative radiation and CDK4/6 inhibitor therapy have conflicting results regarding toxicity, depending on the dose/fractionation of radiation and the regions targeted in the metastatic setting (visceral organs; refs. 61 64 ). Reassuringly, to our knowledge, no studies to date have demonstrated more pronounced side effects of CDK4/6 inhibitors, such as cytopenias and skin desquamation, in women receiving concurrent therapy to the breast or axillary regions.…”
Section: Discussionmentioning
confidence: 99%